Influence of lived experience on risk perception among women who received a breast cancer polygenic risk score: 'Another piece of the pie'. Issue 3 (19th January 2021) - Willis, Amanda M.; Smith, Sian K.; Meiser, Bettina; James, Paul A.; Ballinger, Mandy L.; Thomas, David M.; Yanes, Tatiane; Young, Mary‐Anne
Abstract: Polygenic risk scores (PRS) are personalized assessments of disease risk based on the cumulative effect of common low‐risk genetic variants. PRS have been shown to accurately predict women's breast cancer risk and are likely to be incorporated into personalized breast cancer risk management programs. However, there are few studies investigating the individual impact of receiving a breast cancer PRS. Existing studies have not demonstrated significant changes in perceived risk or risk management behaviors after receipt of polygenic risk information. The aim of this qualitative study was to explore how women with a family history of breast cancer construct breast cancer risk perceptions after receipt of a breast cancer PRS. Unaffected women with a family history of breast cancer who had not previously received genetic counseling regarding their breast cancer risk were invited to participate in this study. In‐depth, semi‐structured interviews were conducted with 20 women who attended a familial cancer clinic in the Australian states of Victoria and Tasmania. Data were analyzed using an inductive thematic approach. Women's lived experience played a significant role in the construction and maintenance of their breast cancer risk perception. Women's pre‐existing risk perceptions were informed by their family history and their knowledge that breast cancer is a multifactorial disease. Knowing that breast cancer is a multifactorial disease enabled most women to integrate genetic information with their pre‐existing notions of risk. Women reported that the information they received was consistent with their existing notions of personal risk and screening advice. Therefore, the PRS did not lead to a change in perceived risk or risk management behaviors for most women. The results of this study provide insight into how polygenic risk information is integrated with pre‐existing notions of risk, which will inform its implementation into clinical practice.